Biofouling of spiral wound membrane sytems. - Vrouwenvelder, Johannes Simon, ....-; Kruithof, Joop, ....-; Van Loosdrecht, Mark C. M. (Marinus Cornelis Maria), 1959- (London : IWA, 2011)
High quality drinking water can be produced with membrane filtration processes like reverse osmosis (RO) and nanofiltration (NF). As the global demand for fresh clean water is increasing, these membrane technologies are increasingly important. One of the most serious problems in RO/NF applications is biofouling - excessive growth of biomass - affecting the performance of the RO/NF systems. This can be due to the increase in pressure drop across membrane elements (feed-concentrate channel), the decrease in membrane permeability or the increase in salt passage. These phenomena result in the need to increase the feed pressure to maintain constant production and to clean the membrane elements chemically. This book relates biomass accumulation in spiral wound RO and NF membrane elements with membrane performance and hydrodynamics and determines parameters influencing biofouling. It focuses on the development of biomass in the feed-concentrate (feed-spacer) channel and its effect on pressure drop and flow distribution. It can be used to develop an integral strategy to control biofouling in spiral wound membrane systems. Most past and present methods to control biofouling have not been very successful. An overview of several potential complementary approaches to solve biofouling is given and an integrated approach for biofouling control is proposed.
Keywords: Biobrandstoffen